Hydroxytamoxifen interaction with human erythrocyte membrane and induction of permeabilization and subsequent hemolysis - Cruz Silva, M. M. (2001)
4-Hydroxytamoxifen (OHTAM) is the most active metabolite of the widely prescribed anticancer drug tamoxifen (TAM) used in breast cancer therapy. This work describes the effects of OHTAM on isolated human erythrocytes, using standardized test conditions, to check for a putative contribution to the TAM-induced hemolysis and to study basic mechanisms involved in the interaction of OHTAM with cell membranes. Incubation of isolated human erythrocytes with relatively high concentrations of OHTAM results in a concentration-dependent hemolysis, its hemolytic effect being about one-third of that induced by TAM. OHTAM-induced hemolysis is prevented by either [alpha]-tocopherol ([alpha]-T) or [alpha]-tocopherol acetate ([alpha]-TAc) and it occurs in the absence of oxygen consumption and hemoglobin oxidation, ruling out the oxidative damage of erythrocytes. However, OHTAM remarkably increases the osmotic fragility of erythrocytes, increasing the susceptibility of erythrocytes to hypotonic lysis. Additionally, the hemoglobin release induced by OHTAM is preceded by a rapid efflux of intracellular K+. Therefore, our data suggest that OHTAM-induced hemolysis does not contribute to TAM-induced hemolytic anemia and it is a much weaker toxic drug as compared with TAM. Moreover, at variance with the membrane disrupting effects of TAM, OHTAM promotes perturbation of the membrane's backbone region due to its strong binding to proteins with consequent formation of membrane paths of permeability to small solutes and retention of large solutes like hemoglobin, followed by osmotic swelling and cell lysis. The prevention of OHTAM-induced hemolysis by [alpha]-T and [alpha]-TAc is probably committed to the permeability sealing resulting from structural stabilization of membrane.